Konsep taman edukasi berbasis aktivitas pelajar di sekolah dasar Islam terpadu Sholahuddin Bogor - Fasa, Balqis Feparima; Fatimah, Indung Sitti (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019DO - 10.24843/JAL.2019.v05.i01.p14, 2019)
Education Garden Design Based on Students’ activity in Advanced Moslem Elementary Sholahuddin Bogor. This research has purpose to detect landscape condition and usage in the specific school environment as a study that influence because of the user activity. There is a main idea to discuss, it is to create a suitable landscape that capable of accomodating the students activity that can affected the learning process so the student will be avoided by unnecessary stress caused by the long duration spent at school based on Islamic garden concept. Several methods will be used in this study, they are field survey, some of which are analysis, syntesis, and desigining methods. Field survey will be used to get primary data and acknowledge the student’s activities and needs. This research is expected to be a recommendation design planning to create a better use for the school landscape that would be suitable and cope with the student’s needs.